Safe Return - Meredeth A. Rowe (EDIS)
In the United States, more than 10,000 times each year, persons with dementia become lost in their own community and cannot find their way home. In this document we will take a look at why people with dementia become lost, how to prevent this from happening, and identify the best search strategies for finding someone who is lost. This document is FCS2211 FY626, one of a series of publications from the distance education in-service "Aging in the 21st Century." First published: September 2003.